Assessment of genomic diversity and population sub-structuring of kingklip (Genypterus capensis) off Southern Africa - Schulze, Melissa Jane (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.